Mensuração de desempenho: uma proposta de melhoria à metodologia do "Balanced Score Card" - Santos, José Francisco dos (2006)
The present moment induces to the adoption, by the companies, of a system of performance management, which considers the market competitiveness and the strategies chosen by the companies, in order to achieve its objectives inside the market. The performance measures, when interrelate mission, strategy, targets and process analysis of the company, guided by the customer satisfaction on products and services provided, become a fundamental factor to manage the organizations. This dissertation has the objective of proposing an improvement of the model of process performance measurement based on the Balanced Score Card model, aimed to contribute on how to operating the model and, at the same time, present a simulation application of the model to an economic segment of business. This work, based on the theoretical system of BSC, presents a proposal of an improved model which aims, as from the adoption of the fifth perspective, the use of the critical success factors of the company, together with the use of the key sectors laid down by the Management by Objectives, identify and structure its strategic indicators; besides, it establishes routines of continual updating of that structure, considering the tactical and strategic feedback. The proposed model intends to be used by a company, belonging to the chemical distribution economic segment, inside the Brazilian market